DEVELOPMENT OF UNIVERSITY AS A COMPETITIVE EDUCATIONAL ORGANIZATION - Ekaterina E. Shishlova; Anzhelika M. Mirzoeva (Высшее образование в России, 2016)
The article proves the need for new forms of organization of universities, the relevant market economy and information society. The authors analyze innovative activities of MGIMO-University, which trains specialists for civil service and business structures actively developing organizational and content bases of educational and scientific activities. The article considers the provisions of the Law on Education of the Russian Federation concerning the activities of educational institutions and management. The use of the term "university as an educational organization" symbolizes the transition to a new paradigm of organization and management of university development, which allows it to be competitive in the new environment.